Smart Monitoring of Potato Crop: A Cyber-Physical System Architecture Model in the Field of Precision Agriculture - Rad, Ciprian-Radu; Hancu, Olimpiu; Takacs, Ioana-Alexandra; Olteanu, Gheorghe (Agriculture and agricultural science procedia, 2015)
In the last two decades an intense shift from advanced mechatronic systems to Cyber-Physical Systems (CPS) is taking place. CPS will play an important role in the field of precision agriculture and it is expected to improve productivity in order to feed the world and prevent starvation. In order to expedite and accelerate the realization of CPS in the field of precision agriculture it is necessary to develop methods, tools, hardware and software components based upon transdisciplinary approaches, along with validation of the principles via prototypes and test beds. In this context this paper presents a precision agricultural management integrated system architecture based on CPS design technology.